GUARANTEE THE GENETIC DAMAGE RESULTED FROM THE PEACEFUL USE OF ATOMIC ENERGY: (COMPARATIVE ANALYTICAL STUDY) - Hussein Ali, Riyadh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The first approach is the laws of criminalization the medical intervention that compromises the integrity of the human genetic map unless the purpose is therapeutic. As for the second approach, it subjects any cause of harm (a harmful act) affecting the genetic formation, to responsibility for its illegal action, which is relating the damage that occurs to the human genome outside the contractual relationship, especially the damages resulting from the harmful act resulting from the peaceful use of atomic energy, which is the subject of the current study. The study scope is determined in identifying the legal problems raised by the subject of the human genome and its genetic map as an attempt to reach legal solutions to them, whether by referring to the traditional legislation in civil law, and if the latter does not meet this, new legal rules are adopted that are consistent with the special nature of the information included in the genetic map.